Semiotic Analysis of Motivational Messages in the Lyrics of the Song I’m Fine by BTS - Kaulika, Adinya Kalya; Sakinah, R. Myrna Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Music has the power to convey meaningful messages, including motivational messages. Using Ferdinand de Saussure’s semiotic theory, this research examines the motivational messages in the lyrics of the song I’m Fine by BTS. The primary focus of this research is on how meaning is produced through the signifier and signified relationship. This research employs an interpretive qualitative approach to delve deep into the social phenomenon. The semiotic approach allows the researchers to explain how signs in song lyrics function in bringing motivational messages. Data were gathered from the lyrics of the song I’m Fine and analysed thoroughly by dissecting the relationship between signifier and signified. This research discovered the hidden messages the songwriter wanted to convey to the listeners. The results show that this song conveys the value of having courage when facing challenges, mental toughness when facing difficulties, and the ability to bounce back from them. This encourages listeners to be optimistic, not to give up, and instead keep trying despite the obstacles. This research proves that song lyrics in the song I’m Fine by BTS were not merely a musical work but also a medium for conveying powerful inspirational messages: one can achieve inner peace and emotional resilience by pushing through life’s challenges with courage.